Understanding of Chemicai Formulae And Nomenclature Of Inorganic Compounds Using Improvised Conceptual Models Among Teacher-Trainees In Offinso And Atebubu Colleges Of Education In Ghana (International Journal of Scientific Research and Management (IJSRM), 2018)
The study aimed at enhancing the understanding of SHS students in chemical formulae and nomenclature using locally constructed conceptual models. It was carried out in Offinso and Atebubu Colleges of Education. The research instrument used was pretest and protest on an experimental and control group with 200 students as sample size. Developmental research design with cluster and purposive sampling techniques were employed. Five research questions were formulated out of which four were modified into null hypothesis and was tested using 2-tailed t-test at 0.05 level of significance. The research results have showed that the use of conceptual models enhanced the understanding of Teacher-trainees in chemical formulae and nomenclature. Additionally, it was found out that the conceptual models had no influence on gender or cognitive capability. This emphasized that conceptual models should be used to assist the teaching and learning of chemical formulae and nomenclature.